TEACHER’S ORAL FEEDBACK TOWARDS STUDENTS’ RESPONSE IN SPEAKING SKILL AT SMKS ERIA MEDAN - Fransiska Samosir; Sumarsih Sumarsih (Universitas Negeri Medan, 2022)
The purpose of this study was to describe and to explain teacher’s Oral Feedback toward students’ response in speaking skill at SMKS Eria Medan. The subject were the students of SMKS Eria Medan from eleventh grade. The types of oral feedback such as positive feedback praise, corrective feedback, recast feedback, explicit correction feedback, elicitation feedback, metalinguistic feedback, repetition feedback and clarification request feedback. The types of feedback that given by the English teacher such as: praise feedback, recast feedback, repetition feedback and metalinguistics (elicitation).There were five reasons why the teacher using the oral feedback: It gives both the teacher and the students information, appreciate the students, it providing direction to students, it providing language input to students, it encouraged students to learn, it encouraged students to be selfsufficient. Teacher might need to apply and know the types of feedback that are appropriate to improve students’ achievement in learning English. However, not all teachers are aware of what type of feedback they use in their classroom and preferred by their students to improve the students English language achievement. The result of the research showed that the English teacher mostly used the directly feedback when give feedback to the students. The researcher used observation and interview for collecting the data.